Superconductivity - Poole, Charles P.; Farach, Horacio A.; Creswick, Richard J.; Prozorov, Ruslan (Amsterdam : Elsevier Science, 2014)
Superconductivity, Third Edition is an encyclopedic treatment of all aspects of the subject, from classic materials to fullerenes. Emphasis is on balanced coverage, with a comprehensive reference list and significant graphics from all areas of the published literature. Widely used theoretical approaches are explained in detail. Topics of special interest include high temperature superconductors, spectroscopy, critical states, transport properties, and tunneling. This book covers the whole field of superconductivity from both the theoretical and the experimental point of view.
Properties of the normal state; Phenomenon of superconductivity; Transport properties; Thermodynamic properties; Magnetic properties; Landau phenomenological theory; Bardeen-Cooper-Schrieffer microscopic theory; Type I superconductivity and the intermediate state; Type II superconductivity; Irreversible magnetic properties; Magnetic penetration depth; Upper critical field with magnetic and non-magnetic scattering; Energy gap and tunneling; Spectroscopic properties; Classical superconductors; Cuprate high-Tc superconductors; Noncuprate superconductors; London penetration depth in iron base superconductors.
Print version record.
Keywords: Superconductivity; SCIENCE -- Earth Sciences -- General; Superconductivity; Electronic books